A Practical Approach for Quantifying Country Risk on the Ukrainian Stock Market - Khomenko, Ya.V.; Molchanov, O.I.; Sheyka, K.S. (Економічний вісник Донбасу, 2013)
This article represents the theoretical basis of country risk evaluating for emerging markets. It also contains the results of testing modified CAPM which include country risk premium for Ukrainian stock market. The study is based on data from the Ukrainian Stock Exchange and UX index for 2009 - 2011. У цій статті відображено теоретичні основи розрахунків ризику країни для ринків, що розвиваються, а також результати тестування модифікованих з урахуванням ризику країни CAMP для українського фондового ринку. Дослідження базується на даних Українській фондовій біржі та індексу UX за 2009 - 2011. В данной статье отображены теоретические основы расчетов странового риска для развивающихся рынков, а также результаты тестирования модифицированных с учетом странового риска CAMP для украинского фондового рынка. Исследование базируется на данных Украинской фондовой биржи и индекса UX за 2009 - 2011.